PELAKSANAAN GROSSE AKTA SEBAGAI PENGAKUAN HUTANG APABILA TERJADI WANPRESTASI (STUDI PADA PERUSAHAAN PEMBIAYAAN NON BANK) - Siti Umamah (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT In implementation or implementation it is not easy to determine whether the proposed deed grosse has met both formal and material requirements. Especially regarding the material requirements of the grosse deed. In practice many cause problems because of the development in msayarakat existence grosse deed based on credit agreement from the bank as the principal agreement. Grosse deed of debt acknowledgment with other agreements in the form of power of sale and / or the power of putting mortgage rights and others in one grosse deed is not allowed for causing rancaunya in execution execution, that is whether execution executed to grosse deed of recognition of debt or to certificate of mortgage . So that this violates the rule of law which is regulated in article 224 HIR and fatwa MA. 213/229/85 / UM-TU / Pdt dated April 16, 1985 so that the grosse aktapakuan of debt is not purely recognition of debtors debtors to a certain amount of creditors and cause grosse deed of recognition of the debt is void by law and the implementation of execution can not be implemented. And concerning repayment payments, interest and penalties and other expenses for the execution expenses incurred in a grosse deed of debt acknowledgment can not be justified in accordance with the nature of the grosse deed which must be purely a one-sided statement from the debtor who admits to owe a certain sum to the creditor With the rules of article 224 HIR and fatwa MA no. 213/229/85 / UM-TU / Pdt dated April 16, 1985, while the clause on payment of installments, interest and penalties and other expenses for execution fee should be included in the credit agreement deed only. The procedure of grosse execution of the debt recognition deed does not have to go through the District Court, but in practice it occurs that the request for a grosse deed of debt recognition must pass through the court process first and can not be directly executed by the execution of the debt recognition grosse and this takes a long time. Meanwhile, the government bank of Bank Rakyat Indonesia of East Kutai Branch will be submitted to KP2LN and PUPN, even if the lawsuit filed a civil suit to the District Court then the Court should not refuse on the grounds not the authority of the Court.